The effect of 40 years of effluent irrigation on soil and pasture properties of the Lactose New Zealand land treatment site : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Applied Science, Soil and Earth Sciences Group, Institute of Natural Resources, Massey University - Robinson, Blair P (Massey University, 2000)
The Lactose New Zealand (LNZ) manufacturing plant, situated in South Taranaki, has an annual average daily effluent output of 1400-1600 m3, over 11 months of the year. Total effluent loading rates are approximately 5000 m3 ha-1 yr-1 . Effluent composition is extremely variable and characterised by high levels of suspended solids, BOD5, COD, K, total P and Na and low pH. Land treatment of effluent has been occurring for approximately forty years and currently effluent is irrigated onto three dairy farms in the vicinity of the manufacturing plant. LNZ has experienced some difficulties in operating and managing both the land treatment system and the dairy farms. Problems have related to the degradation of soil, pasture, surface water and groundwater quality. This study aims to describe the current status of the land treatment system through characterisation of the soil and pasture resource. Factors examined included soil physical, chemical and biological properties, the quality of pasture and the effect of a grazing event on some soil properties. This study has identified some trends that can be used to estimate the rate of change in soil properties due to the addition of effluent under the present conditions. There is the risk of a further decrease in soil bulk density, combined with increased soil moisture content, resulting in treading damage by grazing animals. The soil system still has a very large capacity to fix phosphate. However, of some concern in the likelihood of surface runoff containing high concentration of P as a result of high levels of available P in the top 0-7.5 cm. The current policy of planting riparian strips should reduce this environmental threat. The study suggests that forty years of effluent irrigation has had a considerable effect on soil, pasture and groundwater and surface water quality at the LNZ site. The system will require careful management to ensure the sustainable land treatment of LNZ effluent. Alternative management options are discussed.
Keywords: Soils; New Zealand; Soil degradation; Sewage disposal in the ground; Organic wastes as fertilizer; South Taranaki District